2004
DOI: 10.1158/1535-7163.1451.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipase A2 as a tumor-specific trigger for targeted delivery of a novel class of liposomal prodrug anticancer etherlipids

Abstract: The use of many common clinically relevant chemotherapeutics is often limited due to insufficient delivery to the tumor and dose-limiting systemic toxicities. Therefore, therapeutics that specifically target tumor cells and are nontoxic to normal cells are required. Here, we report the development of a novel class of liposomes composed of lipid prodrugs, which use the increased secretory phospholipase A2 type IIA (sPLA2) activity of the tumor microenvironment as a trigger for the release of anticancer etherlip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Then, we chose the Colo205 xenograft tumor model to test the feasibility of the nanoprobes for the detection of endogenous PLA2. Previous studies suggested that PLA2 was overexpressed in the Colo205 xenograft tumor model. As shown in Figure a, 1 h postinjection, the 19 F MRI signal could be observed with low intensity, which became much stronger 3 h postinjection. Meanwhile, similar experiments were carried out with a healthy mouse.…”
Section: Results and Discussionmentioning
confidence: 70%
“…Then, we chose the Colo205 xenograft tumor model to test the feasibility of the nanoprobes for the detection of endogenous PLA2. Previous studies suggested that PLA2 was overexpressed in the Colo205 xenograft tumor model. As shown in Figure a, 1 h postinjection, the 19 F MRI signal could be observed with low intensity, which became much stronger 3 h postinjection. Meanwhile, similar experiments were carried out with a healthy mouse.…”
Section: Results and Discussionmentioning
confidence: 70%
“…AELs exhibit cytotoxicity and inhibit cell growth. , However, the toxicity of AELs is limited to the target site because a high concentration of sPLA 2 (enough for degradation of liposomes) is found only in the tumor site. It has also been demonstrated that proAEL liposomes lacked hemolytic effect and systemic toxicity compared to a potent AEL (ET-18-OCH 3 ) in vivo and in vitro. , …”
Section: Extracellular Enzymesmentioning
confidence: 99%
“…It has also been demonstrated that proAEL liposomes lacked hemolytic effect and systemic toxicity compared to a potent AEL (ET-18-OCH 3 ) in vivo and in vitro. 75,76 Overall, liposomes are good carriers for targeted delivery of lipid-based prodrugs to tumor sites. Prodrugs are converted into active drug at the tumor site by sPLA 2 .…”
Section: ■ Extracellular Enzymesmentioning
confidence: 99%
“…To address this issue, liposomes were fabricated with an enzymatically degradable unit sensitive to phospholipase A 2 , which exists in high concentrations around tumors . The concept behind delivery of an enzymatically targeted system is intriguing, and preclinical work showed reduction in tumors with minimal side effects noted beyond weight loss (5% in the liposomal group versus 3% in the control on day 1) .…”
Section: Using Nanomaterials To Track Treatmentsmentioning
confidence: 99%